Transcranial Direct Current Stimulation Does Not Counteract Cognitive Fatigue, but Induces Sleepiness and an Inter-Hemispheric Shift in Brain Oxygenation - Borragán, Guillermo; Gilson, Médhi; Guerrero-Mosquera, Carlos; Di Ricci, Eleonora; Slama, Hichem; Peigneux, Philippe (Frontiers in Psychology, 2018)
Sustained cognitive demands may result in cognitive fatigue (CF), eventually leading to decreased behavioral performance, and depletion in available brain resources. In the present study, we tested the hypothesis that transcranial direct current stimulation (tDCS) would counteract the behavioral and neurophysiological effects of CF. 20 young healthy participants were tested in a within-subject counterbalanced order across two different days. tDCS (real vs. sham) was applied over the left prefrontal cortex. Cortical brain activity changes were measured using functional Near Infrared Spectroscopy (fNIRS). CF was triggered using the TloadDback task, a sustained working memory paradigm that allows tailoring task demands according to the maximal cognitive capacity of each individual. Sustained cognitive load-related effects were assessed using pre- versus post-task subjective fatigue and sleepiness scales, evolution of performance accuracy within the task, indirect markers of dopaminergic activity (eye blinks), and cortical oxygenation changes (fNIRS) both during the task and pre- and post-task resting state periods. Results consistently disclosed CF-related effects on all parameters, suggesting a depletion of cerebral resources with time. In the control (sham tDCS) condition, Cerebral Oxygen Exchange (COE) levels increased in the right hemisphere during the resting state immediately after the induction of CF. In the tDCS condition, COE interhemispheric asymmetry reversed. Reduced brain activity in the stimulated hemisphere after a recovery period was associated with increased self-reported sleepiness in the tDCS condition only. Transcranial DCS was not effective to counteract the behavioral effects of CF. However, tDCS combined with CF induction shifted interhemispheric oxygenation balance during the post-training resting state, possibly representing a compensatory mechanism to optimize the allocation of available cognitive resources. Increased self-reported sleepiness associated with brain activity in the stimulated hemisphere after recovery from CF in the tDCS condition may represent negative middle-term tDCS effects.